2021
DOI: 10.1371/journal.pone.0253552
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence as a mediator in the relationship between academic performance and burnout in high school students

Abstract: Low performance of high school students and repeating a year are major problems in the education system. Low performance in the classroom generates negative emotions in young people and has been related to development of school burnout. The objective of this study was to analyze the repercussions of academic performance on burnout in high school students, and establish the role of emotional intelligence in this relationship. The sample was made up of 1287 high school students aged 14 to 18, who filled out ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
1
16
0
2
Order By: Relevance
“…Furthermore, our research found that academic performance was a protective factor against burnout in adolescents. Previous research found that high academic performance was associated with positive emotions, while lower performance was related to negative feelings 44. In addition, adolescents with high academic performance had better academic adaptability, and this adaptability can promote interest in learning, relieve psychological stress and affect mental health 45.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, our research found that academic performance was a protective factor against burnout in adolescents. Previous research found that high academic performance was associated with positive emotions, while lower performance was related to negative feelings 44. In addition, adolescents with high academic performance had better academic adaptability, and this adaptability can promote interest in learning, relieve psychological stress and affect mental health 45.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research found that high academic performance was associated with positive emotions, while lower performance was related to negative feelings. 44 In addition, adolescents with high academic performance had better academic adaptability, and this adaptability can promote interest in learning, relieve psychological stress and affect mental health. 45 The research by Shadid et al showed that the lower grade point average students performed, the significantly greater was academic burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the stress EI dimension, it was related to the inhibition of the EF dimension in this study, but no differences were found between profiles. In this sense, Molero-Jurado et al (2021) analysed the impact of PA with burnout and emotional competences in adolescent students, showing that low PA affected the level of burnout and that stress management and mood in EI acted as mediators in this relationship, proposing EI programmes in the educational context for preventing burnout. These results reinforce the relationship between cognitive abilities, academic competencies and emotional competencies that could have positive consequences on learning (Barkley, 2001;Moreno-G omez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, LPA-based differences in PSQI scores were estimated by Bayesian Factor. The Cauchy prior width was set at 0.7, which indicates a 70% probability of the actual effect size being between –0.5 and 0.5 ( Molero Jurado et al, 2021 ). The Bayes factor value greater than 10 indicates strong relative evidence for a hypothesis ( Quintana and Williams, 2018 ).…”
Section: Methodsmentioning
confidence: 99%